A Implementation of the Tikrar Method in the Development ofQur'an Memorization at Ma'had Tahfizhul Qur'an Annisa Malang - Izza Awal Afnia Izza Awal Afnia (STAI Ma'had Aly Al-Hikam Malang, 2025)
This study aims to describe the implementation of the tikrar method in the development of Al-Qur’an memorization at Ma'had Tahfizhul Qur'an Annisa Malang, as well as to determine its effectiveness and the supporting and inhibiting factors of its application. The type of research used is qualitative research with a descriptive approach. Data were obtained through observation, interviews, and documentation involving caregivers, supervising female teachers (ustadzah), and female students who memorize the Qur’an. The research results show that the tikrar method—namely, a method of repeatedly reviewing memorization with correct and measured recitation—is applied systematically through three stages: (1) individual repetition before submitting memorization (personal review), (2) paired or small group repetition, and (3) repetition together with the supervising ustadzah. The implementation of this method has been proven to improve the quality of students' memorization in terms of accurate pronunciation, fluency, and long-term retention. Factors The main supporters for the implementation of the Tikrar method include schedule discipline, a conducive environment, and intensive guidance from mentors. The inhibiting factors, on the other hand, include student fatigue, limited time, and differences in individual memory capacity. Thus, the Tikrar method can be classified as an effective and relevant method in the development of tahfizh in the Ma'had Tahfizhul Qur'an Annisa Malang environment.